PENGARUH PROMOTION MIX DAN PERCEIVED PRICE TERHADAP VISIT INTENTION SERTA IMPLIKASINYA TERHADAP WILLINGNESS TO RECOMMENDATION (Kajian Pada Museum-Museum di Kota Bandung) - Nur Endah Retno Wuryandari (Universitas Mercu Buana, 2014)
Abstract: The purpose of this study is to understand the variables that affect the willingness to recommendation to visit the museum. So the executive of the museum will know how important exogenous variable promotion mix and variable of perceived price can lead to visit intention as an intervening variable and its implications for willingness to recommendation as the exogenous variables. Instrument in this studyused a questionnaire for 237 respondents through purposive sampling. Data processing techniques using the Structural Equation Model (SEM) with the LISREL program (Linear Structural Relationship). The results showed that the promotion mix and the perceived price variable significantly affect the variable visit intention. Intention to visit variable affects willingness to visit recommendation variable, then the variable of perceived price affecting willingness to recommendation. While the perceived price variable has no direct effect on the variable willingness to recommendationt. The conclusion of this study shows that to increase the visit intention and willingness to recommendation to visit the museum, the executive of museum should focus on the museum promotion mix, especially on the museum guide that could explain the object in complete, exciting and fun, so that it can be a major consideration for visitors torecommendation to others.Keywords: museum, promotion mix, perceived price, visit intention, willingness torecommendation.